“Implementación de un equipo cortador por plasma láser para aceros ASTM A36, A588, en la carrera de electromecánica de la Universidad Técnica de Cotopaxi - Extensión La Maná”. - Paredes Loor, Roddy Lenin (2022)
The main purpose of this project is to implement a láser plasma cutting equipment for ASTM A36, A588 steels, in the Electromechanics career of the Technical University of Cotopaxi - La Maná Extension, which will allow improving the cutting processes in steel parts and improve the capacity for highly complex jobs, in addition to equipping the Electromechanics career with technified equipment to automate their cutting and manufacturing processes. Several tests were carried out on steel sheets and specimens, which were able to cut in a single pass, sheets from 2 mm to 10 and 12 mm thick, with a duty cycle of 60% and a power factor of 80%, at a speed of 6,000 m/s which reduces the metal to steam and molten slag. From the results obtained through the manifested methodology, it will be extended that the implementation of a láser plasma cutting equipment will allow students to know the process, treatment and cutting machinability in various types of ASTM A36 and A588 steel parts, thus improving their quality and design, which will allow them to show not only their theoretical knowledge but also their practical knowledge regarding the use and management of this type of equipment.